Indigenizing the internet - Madsen, Deborah Lea (Cambridge University Press (New York, 2020)
To write of digital indigeneity or digital Natives is to confront the fact that, as Anishinaabe/Métis games designer Elizabeth LaPensée described in a cryptic but resonant tweet: “The Internet has been colonized” (2017 n.pag.). Popularized in the title of Marc Prensky's influential 2001 paper on educational reform, the term “digital Native” is defined by the OED as “A person born or brought up during the age of digital technology and so familiar with computers and the Internet from an early age.” Similarly, artifacts that are created with digital tools and so originate in a digital environment, having no analog equivalent, are called “born-digital” objects. The discursive colonialist violence of cyberspace as a territory inhabited by “indigenous” artifacts and “digital Natives” preempts efforts to discuss the digital creativity of actual Indigenous artists and communities. The digital then is a discursive realm where the profound conflicts generated by settler-colonialism continue to be played out. Indigenous digital interventions pose counter-discourses that oppose the violence of colonialist stereotypes, claiming digital storying as an extension of a form of expression and communication that Indigenous peoples have been using long before the advent of contemporary electronic technology. Indigenizing the digital medium constitutes a powerful message that Natives are not primitive, pre-technological, and “vanishing.” Living Indigenous cultures endure, witnessed by digital creations that work to preserve and disseminate tribal languages in genres of digital storying that perform traditional customs, beliefs, traditions, and values. Indigenous digital storying is a claim to rhetorical sovereignty that articulates Native self-determination through specific ways of knowing and being. Tribal epistemologies express a unique relationship with the world, a relation of interconnection that is performatively enacted in digital genres. This chapter offers close analyses of two dominant “digital Native” forms of storying that use the capabilities of virtual media in conjunction with traditional literary genres to instantiate Indigenous cosmologies: digital film-poems, videopoems, or “poemeos” exemplified by Heid Erdrich's Anishinaabe storying; and Elizabeth LaPensée's Anishinaabe/Métis storying through Indigenously-determined digital narrative or videogames.